Effect of artificial lighting on growth of ipomoea aquatic for indoor hydroponic farming : article / Muhd Muqhzeen Zolkaplie - Zolkaplie, Muhd Muqhzeen (2018)
It is fundamental to every plant requires sunlight to perform photosynthesis. Energy from the sunlight is to convert carbon dioxide and water into molecules needed for growth. Sunlight can be replaced with artificial light with the combination of certain color to replicate the properties of the ray. This way can prevent natural disaster and cloudy days by indoor farming. The effect of artificial light intensity on growth and quality of Ipomoea aquatic using hydroponic system were studied in a low natural light environment. The purposes of this study are to study the growth of Ipomoea aquatic with the suitable combination of LEDs, measure the suitable light intensity and design an automatic LEDs by calibrating the growth with ultrasonic sensor. For the experimental work, the crops were grown in 30 days with the different value of light intensity and number of blue and red LEDs. The result of the experimental work will be used in hardware design. Calibration between the height of the plant with pulse width modulation using ultrasonic sensor and light intensity sensor for the sensors and Arduino Uno as the microcontroller. The design will reduce the work for the user by statically maintain the intensity level in the suitable mode and control the production rate of the crops.